Patients with Mild Traumatic Brain Injury Recruited from Both Hospital and Primary Care Settings: A Controlled Longitudinal Magnetic Resonance Imaging Study - Einarsen, Cathrine Elisabeth (J Neurotrauma, 2019)
With an emphasis on traumatic axonal injury (TAI), frequency and evolution of traumatic intracranial lesions on 3T clinical magnetic resonance imaging (MRI) were assessed in a combined hospital and community-based study of patients with mild traumatic brain injury (mTBI). The findings were related to post-concussion symptoms (PCS) at 3 and 12 months. Prospectively, 194 patients (16–60 years of age) were recruited from the emergency departments at a level 1 trauma center and a municipal outpatient clinic into the Trondheim mTBI follow-up study. MRI was acquired within 72 h (n = 194) and at 3 (n = 165) and 12 months (n = 152) in patients and community controls (n = 78). The protocol included T2, diffusion weighted imaging, fluid attenuated inversion recovery (FLAIR), and susceptibility weighted imaging (SWI). PCS was assessed with British Columbia Post Concussion Symptom Inventory in patients and controls. Traumatic lesions were present in 12% on very early MRI, and in 5% when computed tomography (CT) was negative. TAI was found in 6% and persisted for 12 months on SWI, whereas TAI lesions on FLAIR disappeared or became less conspicuous on follow-up. PCS occurred in 33% of patients with lesions on MRI and in 19% in patients without lesions at 3 months (p = 0.12) and in 21% with lesions and 14% without lesions at 12 months (p = 0.49). Very early MRI depicted cases of TAI in patients with mTBI with microbleeds persisting for 12 months. Patients with traumatic lesions may have a more protracted recovery, but the study was underpowered to detect significant differences for PCS because of the low frequency of trauma-related MRI lesions.